Cardiac autonomic function and cognitive performance in patients with atrial fibrillation. (24th May 2021) - Haemmerle, P; Aeschbacher, S; Springer, A; Eken, C; Coslovsky, M; Dutilh, G; Moschovitis, G; Rodondi, N; Chocano, P; Conen, D; Osswald, S; Kuehne, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Swiss National Science Foundation OnBehalf: Swiss-AF Investigators Background: Atrial fibrillation (AF) is associated with loss of cognition and dementia. Cardiac autonomic dysfunction has been linked to cognitive decline. We aimed to investigate if reduced cardiac autonomic function (CAF) is associated with cognitive impairment in AF patients.  Methods: Patients with paroxysmal, persistent and permanent AF were enrolled from a multicenter cohort study if they presented in AF ("AF group") or in sinus rhythm ("SR group") on a baseline 5-minute ECG recording. Parameters quantifying CAF (heart rate variability triangular index (HRVI), mean heart rate (MHR), the root mean square of successive differences (RMSSD) and the standard deviation of the normal-to-normal intervals (SDNN)) were calculated. We used the Montreal Cognitive Assessment (MoCA) to assess global cognitive function. Results: 1, 685 AF patients with a mean age of 73 ± 8 years, 29% females, were included. The MoCA score was 24.5 ± 3.2 in the AF group (n = 710 patients) and 25.4 ± 3.2 in the SR group (n = 975 patients). After adjusting for multiple confounders, lower HRVI was associated with lower MoCA scores, both in the SR group (β=0.049; 95% confidence interval (CI): 0.016 to 0.081; p = 0.003) and in the AF group (β=0.068; 95% CI: 0.020 to 0.116; p = 0.006). In the AF group, higher MHR was associated with a poorer performance in the MoCA (β=-0.008; 95% CI: -0.014 to -0.002; p = 0.014 ). Other parameters of CAF were not associated with cognition. Conclusion: Our data suggest that impaired CAF is associated with worse cognitive performance in patients with AF. Elderly AF patients with impaired HRVI might undergo cognitive testing in order to screen for cognitive impairment.